DUKUNGAN KESEHATAN JIWA DAN PSIKOSOSIAL DI WILAYAH PESISIR KOTA KENDARI - Umi Rachmawati Wasil Sardjan; Firman Firman; Mimi Yati (Jurnal Abdi Masyarakat, 2022)
The COVID-19 pandemic leaves various kinds of problems, including health problems (physical) and psychosocial problems. The Covid-19 outbreak is a stressor for health workers and the community. Psychosocial problems caused have a wider and longer impact than physical injuries, while attention to mental health is not a priority for handling health problems during the COVID-19 pandemic. Common responses from affected people (directly or indirectly) include fear of falling ill and dying, not wanting to come to health care facilities for fear of being infected while being treated, fear of losing their livelihood, not being able to work during isolation and being expelled from work. Then, they are also afraid of being ostracized by the community/quarantining because they are associated with disease (such as racism because they are considered to come from an affected place), feel powerless to protect loved ones, fear losing loved ones, afraid of being separated from loved ones and influence due to quarantine rules. In addition, people also refuse to take care of young children who are alone or separated, people with disabilities, or elderly for fear of infection because their parents or caregivers are quarantined, feel helpless, bored, lonely, and depressed while isolated, and afraid of experiencing previous outbreaks. The term Mental Health and Psychosocial Support (MHPS) is used in the Inter-Agency Standing Committee (IASC) Guidelines for MHPS in an emergency situation, which means any external or local support to protect or enhance psychological well-being and/or preventing or treating mental health conditions.